A study on the occurrence of drought at Hebbal - SURYANARAYANA, G.; RAJASHEKARA, B. G.; JAGANNATH, M. K.; KULKARNI, K. R. (MAUSAM, 1971)
Rainfall data of seventy-one years of Agricultural Research Station, Hebbal, Bangalore have been made use to study the rainfall distribution and occurrence of drought. Out of several classifications and groupings of rainfall, "decile" grouping found to be the best for any analysis. The percentage of rainy days, number of dry spells during the cropping season and coefficient of variability in the amount of rainfall were found to be the important factors affecting the severity of drought. Using these factors along with crop-soil-water relationships a tentative definition of drought for south eastern parts of Mysore State has been drawn.